Hazards and incident investigation at palm oil mill industry - Chen, Chit Wee; Ting, Joseph Zhi Ho; Mahmood, Salwa; Khalid, Amir; Jaat, Norrizam; Basharie, Siti Mariam (Penerbit UTHM, 2020)
Occupational Safety and Health Act (OSHA) is a discipline with broad scope involving many specialized fields. This research was conducted to determine the relationship between the hazards occurring and the control measures to overcome the hazards occur in the Palm Oil Mill located at Ulu Keratong, Segamat, Johor. Nowadays, the workers are lack of safety and health practice from their companies based on the statistics that have shown the number of fatality and permanent disablement cases due to the accident in the palm oil mill. Which causes the accidents and injuries happened due to management control that does not emphasized on the safe practise of workers. Information and data collection were carried out by using HIRARC Form and Preliminary Hazard Analysis (PHA) in the Palm Oil Mill RISDA which will be further discuss in the methodology part. The main objective of this study is to promote adaptable occupational environment and suggest some countermeasures to solve the potential hazard and the consequent responsibilities relevant to professional engineering practice. There were seven hazards have been identified such as crash by rotating machine, struck by heavy palm fruit and slippery floor, excessive heat, excessive pressure of tractor tire, chemical spillage and noise hazard. From the result and findings, the hazards and control measures identified are able to determine improvements in knowledge and risk perceptions among the workers and visitors towards health policies and essential interventions for hazard prevention. Effective job safety and health programs help reduce worker injuries and illness in the long term.